Introversive semiosis in action: depictions in opera rehearsals - Löfgren, Agnes; Emily Hofstetter (My University, 2021)
This paper focuses on how opera rehearsal participants use depictions to accomplish proposals; they use a locally created scene, comprised of concrete embodiments to represent another physically or temporally distant scene. Whereas earlier work investigating depictions in interaction has mainly focused on demonstrations in pedagogical scenarios, this paper will discuss how depictions serve the ongoing creation, and aesthetic negotiation, of a yet-to-be-artistic product. In simultaneously creating and referencing iterations of this artwork, participants’ depictions are both self-referential, in introversive semiosis, as well as externally referencing prototypes of mundane behaviour, in extroversive semiosis. We argue that the negotiations of the extroversive and introversive references through depiction constitute the artistic labour of creating a performance. Furthermore, we suggest that the iterative nature of rehearsing an artistic piece demonstrates analogies between introversive semiosis and interactional techniques for projection and depiction. Opera is accomplished through dynamic collaborative social processes, techniques for which include the depictions described in this paper.